JURNALISME LINGKUNGAN PADA MEDIA MONGABAY : (ANALISIS WACANA KRITIS BERITA INDUSTRI NIKEL ANCAM SULAWESI) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
The research aims to determine the application of environmental journalism in the Mongabay media in accordance with the ethical principles of environmental journalists. First, understand discourse analysis in texts related to news about the nickel industry threatening Sulawesi. Second, discourse practices in creating news texts for the Nickel Industry Threaten Sulawesi. Third, socio-cultural considerations in creating discourse. In this research, the researcher used a qualitative method with Norman Fairclough's critical discourse analysis approach. The research results show that Mongabay Media has applied the ethical principles of environmental journalism in its reporting. Representation in the news text is filled with sentences that take sides with the weak, or those who do not have access to speak in the media. Then the relationship built in the text brings the writer and reader closer together, while in the text, the identity of the Mongabay media is increasingly revealed, with the use of the text taking full sides with the turmoil of damage caused by the nickel industry. The discourse practice used by the Mongabay media in the news about the Nickel Industry Threatening Sulawesi is that there is a similarity in the understanding of media power owners with the ideology of news writers, both playing a role in protecting the environment. The discourse presented in the text is not only an effort to inform Sulawesi's condition due to mining but also to control those who process the mine. Socio-cultural considerations in reading news texts can be seen from the way Mongabay media gives voice to coastal communities, fishermen, indigenous peoples, and women in its text.